2023
DOI: 10.3390/biology12060777
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Inhibit PMA-Induced MMP-9 Expression via microRNA-204-5p Upregulation and Deactivation of NF-κBp65 in Breast Cancer Cells

Abstract: Objective: Breast cancer (BC) is the most common malignancy in females globally. Matrix metalloproteinase-9 (MMP-9) is crucial to the invasion, progression and spread of BC. Gold nanoparticles (AuNPs) have an anti-tumorigenic role, but their therapeutic role in microRNAs (miRNAs) regulation has not been explored. This study determined the potential of AuNPs against MMP-9 overexpression/production and miRNA-204-5p regulation in BC cells. Methods: AuNPs were newly engineered, and their stability was analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…PMA induces MMP-9 expression via a protein kinase Cα(PKCα)-dependent signaling cascade in BEAS-2B human lung epithelial cells (Shin et al 2007). Stimulation of MCF-7 cells with PMA significantly downregulated the expression of hsa-miR-204-5p and significantly upregulated the mRNA expression of human MMP-9 (Farhana et al 2023). An interesting future direction would be to explore whether part of Thiram’s MOA involved upregulation of MMP-9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…PMA induces MMP-9 expression via a protein kinase Cα(PKCα)-dependent signaling cascade in BEAS-2B human lung epithelial cells (Shin et al 2007). Stimulation of MCF-7 cells with PMA significantly downregulated the expression of hsa-miR-204-5p and significantly upregulated the mRNA expression of human MMP-9 (Farhana et al 2023). An interesting future direction would be to explore whether part of Thiram’s MOA involved upregulation of MMP-9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNAs are involved in the modulation of EMT, a crucial process in cancer metastasis [18,19]. Altered miRNA expression profiles have been associated with BC subtypes, clinical outcomes, and therapeutic responses [27,34,35]. Understanding the role of miRNAs in BC can provide insights into the underlying molecular mechanisms and aid in the development of diagnostic tools and targeted therapies for improved patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Gold nanoparticles (GNP) have gained considerable attention in medical applications due to their unique physicochemical properties and biocompatibility. These nanoscale particles, typically ranging from 1 to 100 nanometers in size, exhibit excellent stability, high surface area-to-volume ratio, and tunable optical properties [34,35]. GNP can be easily functionalized with various molecules, making them versatile platforms for targeted drug delivery, imaging, and therapy [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear Transcription factor, NFκB, is a potent inflammatory signaling pathway involved in numerous pathogenic processes and the treatment of cancers. Activation of NFκB signaling via its subunit p65 and/or p50 has been involved in tumorigenesis and has now been well considered one of the best targets for cancer therapy ( 61 , 62 ). This study, demonstrated a significant increase in the levels of NF-κBp65 and NF-κBp50 subunits in the nuclear extract of MDA-MB-231 cells treated with IFN-γ alone for 30 minutes.…”
Section: Discussionmentioning
confidence: 99%